Casting lights and shadows on designed spaces - Abdul Shukor, Shureen Faris (Universiti Putra Malaysia Press, 2017)
I see designers as people who are capable of setting the stage for the space we live in. Just like a stage setting, the mood has to be set and the actors/ users of a space should be allowed to contribute to the overall mood of the play. Before we proceed further, let us delve into the aspects of light for theatre. Four controllable qualities of light are the prerequisites for lighting required for stage. The four qualities are Intensity, Colour, Direction, and Movement.